Comparative study of pyrolytic carbons prepared from printed circuit boards by magnetic and electrostatic separation. Issue 53 (13th October 2021) - Kan, Yujiao; Zheng, Fangyuan; Zhang, Ruxin
Abstract : To discover the influence of separation technologies for PCBs on the preparation, characterization and application of pyrolytic carbon, two kinds of nonmetal fraction from magnetic and electrostatic separation were chosen as the precursors. Abstract : Physical technology is the main method to separate metal and non-metallic fractions from printed circuit boards (PCBs). The non-metallic fractions from magnetic and electrostatic separation have different ingredients, which enables them to be prepared into pyrolytic carbon with different properties. To discover the influence of separation technologies for PCBs on the preparation, characterization and application of pyrolytic carbon, two kinds of nonmetal fraction from magnetic and electrostatic separation were chosen as the precursors of pyrolytic carbon. The thermogravimetric analysis of non-magnetic fraction and non-conductive fraction at different heating rates was discussed in the paper. The optimal heating rate of 10 °C min −1 was applied in preparing pyrolytic carbons. Pyrolytic carbons prepared from the non-magnetic fraction and non-conductive fraction had visible differences in their morphological and pore structures. Pyrolytic carbons of the non-magnetic fraction exhibited higher BET surface area (313 m 2 g −1 ) and higher adsorption capacities for ciprofloxacin (142.82 mg g −1 ) than those of pyrolytic carbon of the non-conductive fraction ( S BET : 235 m 2 g −1, q m : 78.17 mg g −1 ). Equilibrium data fit better to the Freundlich model than the Langmuir model. According to the calculated thermodynamic parameters, CIP adsorption processes by the two pyrolytic carbons were spontaneous and endothermic. Although the metal recovery from PCBs through electrostatic separation is higher, pyrolytic carbon prepared from the non-magnetic fraction shows better pore characteristics and adsorption properties. This paper might be the first report of the effect of separation technology for PCBs on the preparation of pyrolytic carbons. This paper contributed to the reutilization of non-metallic fractions of PCBs and the development of a cyclic economy.